Creation of Functional Meat Products with the Use of Biomass of Pleurotus ostreatus (Jacq.) P. Kumm., Cultivated by Meal - Peshuk, Ludmila; Krupodorova, Tatiana; Hashchuk, Oleksandra (My University, 2013)
For scientific substantiation of possibility of creation and development of functional products and products of special purpose, in the framework of the state the topic «Development of innovative technologies of meat products with mushroom raw materials нутриєнтно - adequate recreational and prophylactic геродиетическому nutrition» (ETC 0113U001426) at the Department of technology of meat and meat products, conducting research on the use of biomass of fungus, cultivated on the meal medicinal plants in recipes meat products: cooked sausages, sausages, meat loaves. A wide range of studies using mushrooms, cultivated on the substrates of medicinal plants, and creation on their basis of meat products of new generation, consistent with the concept of functional and prophylactic nutrition.
Keywords: биомассы грибов; функциональные продукты и продуктов специального назначения; біомаси грибів; функціональні продукти і продуктів спеціального призначення; biomass of fungi; functional products and products of special purpose; кафедра технології м’яса і м’ясних продуктів